An audit of anesthesia safety in a pediatric cochlear implantation program. Issue 6 (9th January 2015) - Hawksworth, Chris; Ravury, Shyam; Lerman, Jerrold
Summary Background Approximately 50 children per year undergo cochlear implant surgery under the Scottish Cochlear Implant Programme at University Hospital Crosshouse, Kilmarnock. Many have significant comorbidities. Although this district general hospital has a high dependency unit, there is no pediatric intensive care unit (PICU). Children deemed likely to need PICU care are operated on at the local tertiary pediatric hospital in Glasgow, 25 miles away. Objective To determine the safety of anesthesia for cochlear implant surgery in children at a district general hospital. Methods Using the theater management system, we identified 306 cochlear implant procedures in children aged 16 years and under. A retrospective case note review was performed to determine demographic data and seek evidence of any anesthesia‐related complications. Results Records for 168 children having 258 cochlear implant procedures were obtained. Forty percent of these children had one or more comorbidities, including 11.9% who were ex‐premature babies. Twenty‐two complications or incidents were noted, the majority of which were minor. Two cases had potentially serious complications and one of these was abandoned. This gives a serious complication rate of 0.8%. Undeclared upper respiratory tract infections was most likely the greatest preventable cause of complications. Seven cases were referred to the regional pediatric center during the study period. Conclusion Anesthesia for cochlear implants in children can be safely carried out in a district general hospital setting. Appropriate safeguards should be in place to refer complex cases which may require PICU to a tertiary pediatric center.